Optimalisasi Rapid Response Anggota Panji Yosua PKB GMIM Moria Kali & Otniel Kali Selatan Pada Korban Henti Jantung Dan Henti Nafas Lewat Pelatihan BHD Awam - Paat, Toar; Katuuk, Mario Esau; Arianto, Eko (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2024)
Cardiac arrest can occur at any time, anywhere, and is caused by various conditions and environments. Basic Life Support (BHD) measures can minimize the death rate. The presence of competent helpers during a life-threatening emergency can increase the victim's chances of survival. This assistance is not only provided by health workers, but everyone can do BHD, including members of the Panji Yosua Pria Kaum Bapa. This activity aims to equip the members of Panji Yosua Pria Kaum Bapa GMIM Moria Kali dan GMIM Otniel Kali selatan in terms of Rapid Response when encountering victims who experience cardiac arrest and respiratory arrest by providing Basic Life Support. Training activities are carried out by means of education, simulation and demonstration, but leaflets are also provided as an internalization effort for training participants. The results of this community service show that there was an increase in the average knowledge score after Basic Life Support training was carried out.